PEMANFAATAN YOUTUBE SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA DIMASA PANDEMI COVID-19 - mila amelia; Elva Tati Susanti (UJMES (Uninus Journal of Mathematics Education and Science), 2021)
Seeing the education situation in Indonesia in the COVID-19 pandemic, the use of technology has a very significant role in connecting the interaction of educators and students for the distance teaching and learning process, we often call online learning (in the network). Currently the pandemic is a challenge in developing creativity in the use of technology, not only transmitting knowledge, but also how to ensure learning is conveyed properly. Educators need learning media to help the teaching and learning process. Technological developments have a positive impact on education, one of which is the use of Youtube as a medium of information. In this condition, Youtube can be used by educators as a learning medium. This learning media is packaged in the form of a video explaining mathematics material using conventional learning including material presentation, sample questions, working steps to solve math problems, and providing practice questions. The purpose of this paper is to use Youtube for distance learning and help students understand the learning material.